Pengaruh Latihan Jalan Tandem (Tandem Stance) Terhadap Peningkatan Keseimbangan Untuk Mengurangi Risiko Jatuh Pada Lanjut Usia - Rahmadani, Carolina Putri Kusuma, Totok Budi Santoso, S.Fis, M.Ph (2017)
Backgroud: Elderly is a further stage in the process through which the life of every human being characterized by decreased ability and function of the body both physically and psychologically. As a result of physiological changes, then the balance of the elderly to be disrupted. Tandem stance exercise can improve postural balance lateral parts, which play a role in reducing the risk of falls in the elderly. Objective: knowing the effects of tandem stance exercise on improvement of balance to reduce the risk of falls in the elderly in the Geyer Village, Geyer Subdistrict, Grobogan Regency. Methods: This research is a quasi-experimental with the static group comparasion design. The sample was 50 elderly people by using purposive sampling method. Measurement of the balance in the elderly using Time Up and Go Test and measurement of quadriceps muscle strength using Leg Dynamometer. Data were analyzed using Chi Square test. Results: There is a positive effect of tandem stance exercise on improvement of balance after using Chi Square statistical test obtained significant value of 0,015 with TUG, and significant value of 0.009. with Leg Dynamometer. Conclusion: There is a positive effect of tandem stance exercise on improvement of balance to reduce the risk of falls in the elderly in the Geyer Village, Geyer Subdistrict, Grobogan Regency.